MANSONELLIASIS: A BRAZILIAN NEGLECTED DISEASE - Medeiros, Jansen Fernandes; Pessoa, Felipe Arley Costa; Camargo, Luis Marcelo Aranha (Revista de Patologia Tropical / Journal of Tropical Pathology, 2014)
Mansonelliasis is a filariasis whose etiological agents are Mansonella ozzardi, Mansonella perstans and Mansonella streptocerca. Only the first two cited species occur in Brazil. M. ozzardi is widely distributed in Amazonas state and it is found along the rivers Solimões, Purus, Negro and their tributaries while M. perstans is restricted to the Upper Rio Negro. In this update, we report the occurrence of M. ozzardi in Amazonas since the 1950s, and we show that over the years this filariasis has been sustained with high prevalence, while maintaining a constant cycle of transmission in endemic areas due to the lack of treatment and control policies. M. perstans has so far only been recorded in indigenous populations in the Upper Rio Negro. However, the continuous flow of migrants to other regions may cause an expansion of this infection.